Pemberdayaan Masyarakat Desa Kwadungan Dalam Peningkatan Nilai Produk Turunan Bebek Dengan Metode Community-Based Entrepreneurship dan Value Chain Development - Fais Sofyan Noor; Erba Lutfina; Galuh Wilujeng Saraswati; Dhiky Resandi Wur Handoyo (LPPM ITB AAS Indonesia Surakarta, 2026)
Downstream processing of livestock commodities is an important strategy for increasing product value and strengthening community economic independence based on local potential. Kwadungan Village, Ngasem District, Kediri Regency, has potential for herded duck farming, with a population of approximately 6,750 ducks. However, ducks and eggs are still predominantly sold fresh to collectors, resulting in limited added value. This community engagement program aimed to strengthen the capacity of the target group through the downstream processing of duck and egg products using the Community-Based Entrepreneurship (CBE) and Value Chain Development (VCD) approaches. The partner was the BERTAKWA group (Bebek dan Telur Kreasi Kwadungan), consisting of 20 productive-age housewives. The program was implemented through six stages: socialization and target-group mapping, production and packaging training, production assistance, legal compliance assistance, branding and marketing strengthening, and evaluation and sustainability planning. The program resulted in three processed products: black duck sambal, shredded duck, and keripik ketandhok. The participants’ mean knowledge score increased from 52.5 in the pre-test to 88 in the post-test, representing an increase of 35.5 points. The program also strengthened group capacity in production, packaging, business management, legal compliance, branding, and marketing. This program represents an initial step toward strengthening the duck and egg value chain through an integrated and sustainable approach.